Benefits of dance for the health and well-being of youth: comparison with athletes and sedentary. - Celia Marcen; Susana Monserrat-Revillo; Esther Martínez-Domínguez (European Journal of Human Movement, 2024)
This study aimed to enquire about the potential benefits of dance among young people and its relationship to perceived well-being. To this end, this preliminary research juxtaposes a cohort of young dancers with athletes engaged in other sporting activities and a control group of sedentary young people.